"The Team Behind the Team": Exploring the Organizational Stressor Experiences of Sport Science and Management Staff in Elite Sport. Issue 1 (2nd January 2019) - Arnold, Rachel; Collington, Sam; Manley, Hannah; Rees, Samuel; Soanes, James; Williams, Matthew
Abstract : This study explored the organizational stressors encountered by the "team behind the team" (viz., those operating in sport science and management roles) in elite sport and the consequences these can have. Forty support personnel working in elite sport were interviewed. Thematic analyses unveiled 36 lower and 6 higher order themes, which were separated into stressors encountered (e.g., relationship and interpersonal, physical resource, contractual and performance development, organizational structure and logistical) and their consequences (e.g., emotions and outcomes). Building on extant work, this study moves the focus beyond athletes' stress experiences to provide novel insight into those operating in sport science and management roles. The findings offer original insight into the educational needs of sport science and management staff, which can inform practitioners who face increasing demands to work with such personnel, and raise sports organizations' awareness of their duty of care to employees and the factors that need to be managed.